On fixed point results for alpha-implicit contractions in quasi-metric spaces and consequences - Aydi, Hassen; Jellali, Manel; Karapınar, Erdal (Nonlinear Analysis: Modelling and Control, 2016)
In this paper, we prove some fixed point results involving α-implicit contractions in quasi-metric spaces. Moreover, we provide some known results on G-metric spaces. An example and an application on a solution of a nonlinear integral equation are also presented.